Online learning for freshmen: opportunities and challenges in developing English communicative ability - Endang Susilawati (UPT Bahasa Universitas Tanjungpura, 2022)
This research had purposes: to identify (1) the challenges; (2) the opportunities taken by the freshmen; and (3) to analyze the ways they might alternately manipulate the challenges to become opportunities to develop their English communicative ability through online learning. The primary data were taken from questionnaires administered to the freshmen of EESP of FKIP UNTAN registered in academic year 2020/2021. Additional data were also taken from an FGD with the class representations. It was done for the reflection of the online learning process. The findings showed the positive values of these factors: (1) the readiness of the institution for the online learning; (2) the readiness of instructors and administrative staff with the online learning, (3) the readiness of freshmen; and (4) the characteristics of the online learning itself, contributed to the opportunities. Meanwhile, the negative values contributed to the challenges. However, the freshmen were able to manipulate the challenging factors alternately to become opportunities as such that most of them managed to survive for their first-year endurance and finally succeeded to improve their English communicative ability and to achieve satisfactory to very satisfactory level of GPA. Therefore, the online learning modality should be continually applicable in the post-pandemic situation.